The Effectiveness of Curriculum Review in Improving Quality, Relevance, and Students’ Employability in University Education in Uganda - Tagulwa, Elvaida Agnes; Owino, Philip; Muwonge, Francis; Kaahwa, Maria Goretti (Future Science / FSH-PH Publications, 2023)
The study examined the relationship between curriculum review and students’ employability in the faculty of science at Kyambogo University, Uganda. The population comprised of lecturers in the faculty of science and the sample size consisted of 66 full time lecturers. The specific objective of the study was to assess the relationship between curriculum review and students’ employability. Curriculum review was assessed regarding its relevance in developing professional skills, personal skills, and interpersonal skills as important employability skills for students. Quantitative results revealed that there is a positive statistically significant correlation between curriculum review and students’ employability (Professional skills r= 0.766, p=.0.001; Personal skills r=0.596, p=0.356; interpersonal skills, r=0.349, p=0.497). Regression analysis indicated that curriculum review (β = 0.75, P = 0.00) < 0.05) had a strong positive significant effect on students’ employability. Qualitative results revealed that curriculum review is one of the strategies of quality assurance at the programme level; participation of key stakeholders in the curriculum review ensures the quality and relevance of the curriculum; and financial facilitation of curriculum review process motivates higher levels of output. It is therefore recommended that: the University financially facilitates curricula reviews so that key stakeholders get involved to improve the quality and relevance of curricula; Kyambogo University should collaborate and develop partnerships with industries to improve educational innovation, University technology, and promote knowledge transfer from university to industry and society, and consequently enhance students’ employability.